Analysing the Coruña Corpus: Subjectivity and Intersubjectivity Markers - Crespo, Begoña (Studia Anglica Posnaniensia, 2022)
This paper aims to analyse the concepts of subjectivity and intersubjectivity in scientific writing through the use of stance adverbs perhaps and possibly. These adverbs act as markers of the authors’ presence expressing their views, and a covert relationship between these authors and their corresponding readership. The material used for this study includes four sub-corpora of the Coruña Corpus of English Scientific Writing: CETA (Corpus of English Texts on Astronomy), CEPhiT (Corpus of English Philosophy Texts), CHET (Corpus of English History Texts), and CELiST (Corpus of English Life Sciences Texts). Two of these represent the so-called soft sciences, and the other two the hard sciences, which will allow for comparison. The results might argue against the generally-assumed tendency in the history of scientific writing that this discourse has moved from being author-centred to object-centred. Perhaps it is simply impossible for writers of science to disappear completely from their texts.